Bioinformatic approaches for the genetic and phenotypic characterization of a Saccharomyces cerevisiae wine yeast collection - Duarte, Ricardo Franco (2007)
Apresentação efectuada nas "Jornadas de Biologia de Leveduras Professor Nicolau van Uden, 15, Porto, Portugal, 2007."